Togo : 2011 Article IV Consultation and Sixth Review Under the Extended Credit Facility Arrangement: Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report, 2011)
Togo's economic performance continued its gradual improvement, marking progress in overcoming the legacy of its protracted domestic crisis. The program has broadly achieved its objectives for growth and macroeconomic stability. The improving economic performance and sound policies have continued, despite the adverse impact of the global oil price shock, particularly on fiscal policy. The discussions focused on fiscal and structural policies to achieve higher economic growth while maintaining stability. Accelerated structural reforms are key for robust, sustained, and quality growth.